2015
DOI: 10.1016/j.jcv.2014.12.020
|View full text |Cite
|
Sign up to set email alerts
|

WU and KI polyomaviruses in respiratory, blood and urine samples from renal transplant patients

Abstract: 21Background: It is suggested that immunosuppression due to transplantation might be a risk 22

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…BKPyV, JCPyV and TSPyV can be found in the kidney (Doerries, 2006;Fischer et al, 2012), whereas KIPyV, MCPyV, HPyV9 and STLPyV DNA can be detected in urine (Csoma et al, 2012(Csoma et al, , 2015Husseiny et al, 2010;Lim et al, 2013;Mertz et al, 2010;Rockett et al, 2013). The BKPyV, MCPyV and TSPyV early and late promoters were among the strongest in HEK293 cells.…”
Section: Discussionmentioning
confidence: 99%
“…BKPyV, JCPyV and TSPyV can be found in the kidney (Doerries, 2006;Fischer et al, 2012), whereas KIPyV, MCPyV, HPyV9 and STLPyV DNA can be detected in urine (Csoma et al, 2012(Csoma et al, , 2015Husseiny et al, 2010;Lim et al, 2013;Mertz et al, 2010;Rockett et al, 2013). The BKPyV, MCPyV and TSPyV early and late promoters were among the strongest in HEK293 cells.…”
Section: Discussionmentioning
confidence: 99%
“…To detect WU and KI virus DNA, nested and duplex real-time PCRs were carried out with the primers [58,59] and protocols detailed previously [39,40]. Plasmids containing the KIPyV and WUPyV genomes were used as positive controls kindly provided by Tobias Allander from Karolinska Institute (Stockholm, Sweden) and David Wang from Washington University (St. Louis, Miss., USA) [21,60].…”
Section: Methodsmentioning
confidence: 99%
“…Their respiratory transmission is suggested based on prevalence data from numerous studies, as has been summarized in review articles [19,37,38]. Both KI and WU viruses were detected in urine samples, which suggests that these viruses may also infect the urinary tract [39,40,41]. …”
Section: Introductionmentioning
confidence: 99%
“…Intra-assay analysis KIPyV 5 × 10 6 23.00 0.21 0.9 5 × 10 5 25.52 0.27 1.1 5 × 10 4 28.92 0.41 1.4 5 × 10 3 33.12 0.32 1 5 × 10 2 36.81 0.47 1.2 WUPyV 5 × 10 6 22.12 0.37 1.7 5 × 10 5 25.26 0.22 0.9 5 × 10 4 28.56 0.26 0.9 5 × 10 3 32.41 0.22 0.7 5 × 10 2 36.1 0.48 1.3…”
Section: Coefficient Of Variation (%)mentioning
confidence: 99%
“…KIPyV and WUPyV, as the BK and JC polyomaviruses, persist in a latent form in the human body but they could mainly reactivate in patients with immunosuppression. The initial identification of KIPyV and WUPyV in respiratory samples was progressively extended to other human fluids including blood, cerebrospinal fluid, lymphoid tissue, urine, stool and saliva [3][4][5][6]. Serological evaluations demonstrated that the primary infections by KIPyV and WUPyV occur early in life through the respiratory and fecal routes.…”
Section: Introductionmentioning
confidence: 99%